Pengembangan Kemampuan Interaktif dan Reaktif Siswa Dengan Metode Pembelajaran Sosiodrama - Yunitalia Sugiono Putri; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This article is a type of conceptual research that explains how sociodrama learning methods are able to develop students' interactive and reactive abilities. The subject of automation in public relations and protocol management, especially the basic competencies for implementing meetings, aims to enable students to practice how to simulate meetings. In the implementation of learning, the conceptual delivery of material isnt enough to stimulate students' kinesthetic intelligence, and therefore practical activities need to be applied in its application. Sociodrama learning methods are considered appropriate and in accordance with the learning objectives. The sociodrama method is a teaching method conducted by the teacher by providing opportunities for students to play roles using improvised dialogue about social phenomena that occur in the community or experience-based learning in the form of social drama. Sociodrama trains students to express their opinions in meetings, think responsively in problem solving, communicative in interacting, and bring up cooperative attitudes in groups. The review in this article proves that the sociodrama learning method is very influential in the development of students' interactive and reactive abilities.